Associations of gestational weight gain with offspring thinness and obesity: by prepregnancy body mass index - Nianqing Wan; Li Cai; Weiqing Tan; Ting Zhang; Jiewen Yang; Yajun Chen (BMC, 2018)
Abstract Background Previous studies indicated that excessive gestational weight gain (GWG) was positively associated with offspring obesity. Nevertheless, little is known about the effect of GWG on offspring thinness. This study aimed to assess the association of GWG with childhood weight status across the full range of weight status by prepregnancy body mass index (BMI). Methods We used data from a retrospective study of 33,828 Chinese children aged 6-18 years and their mothers. Children's weight and height were objectively measured. Maternal GWG and other information were collected by using self-reported questionnaires. Multivariate linear regressions and logistic regressions were applied. Results Overall, the prevalence of thinness and overweight/obesity in children were 12.9 and 17.3% respectively (p < 0.05). Children's BMI z-score was on average 0.021 higher for every 1-kg greater GWG. For mothers who were underweight or normal weight before pregnancy, excessive GWG was positively associated with offspring overweight/obesity [OR (95% CI): 1.51 (1.21, 1.90) and 1.30 (1.17, 1.45)], whereas inadequate GWG was associated with increased risk of offspring thinness [OR (95% CI): 1.24 (1.05, 1.46) and 1.17 (1.04, 1.32)]. Similar but non-significant associations were found in prepregnancy overweight mothers. Notably, there was a very high prevalence of child overweight/obesity (30.2%) in prepregnancy overweight subgroup regardless of GWG status. Conclusions Inadequate GWG was associated with an increased risk of offspring thinness, whereas excessive GWG was associated with an increased risk of offspring overweight and obesity among prepregnancy underweight and normal weight mothers only.